Congolese women speak: languaging, translanguaging and discursive cross-culturing as resources for empowerment. (4th March 2021) - Brownlie, Siobhan
ABSTRACT: This article presents a writing project undertaken by the author with a small group of French-speaking Congolese women asylum seekers in Manchester, UK. The women wrote stories and poems about their country of origin; a multilingual booklet of their writings was published; and the women did a public performance of their writings. The article studies the project through the prism of languaging (in particular the relationship of discursive interactions with the environment), translanguaging (the use of multiple languages), and discursive cross-culturing (cultural comparisons taking place during interactions). It is found that these three discursive processes served to enhance well-being and empowerment of the women.